2016
DOI: 10.1002/2016gl070810
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional outflow jets generated in collisionless magnetic reconnection

Abstract: The present study proposes a new theoretical model generating three‐dimensional (3‐D) outflow jets in collisionless magnetic reconnection by means of a large‐scale particle‐in‐cell simulation. The key mechanism is the formation of 3‐D flux ropes arising in the turbulent electron current layer formed around the magnetic x line. The scale of the flux ropes along the current density is determined by the wavelength of an electron flow shear mode which is a macroscopic scale larger than the typical kinetic scales. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Recently, Fujimoto (2016) highlighted the intermittent, quasi-turbulent formation and ejection of 3D magnetic island plasmoid flux ropes in a particle-in-cell simulation, obtaining results that are qualitatively similar to the MHD simulation results we present here. Analysis of magnetic reconnection processes at MHD scales is valuable specifically because of the intrinsic coupling of disparate spatial scales associated with the diffusion region and the macroscopic evolution of global system in which the both large-scale magnetic field and bulk plasma dynamics directly influence the reconnection process.…”
supporting
confidence: 77%
“…Recently, Fujimoto (2016) highlighted the intermittent, quasi-turbulent formation and ejection of 3D magnetic island plasmoid flux ropes in a particle-in-cell simulation, obtaining results that are qualitatively similar to the MHD simulation results we present here. Analysis of magnetic reconnection processes at MHD scales is valuable specifically because of the intrinsic coupling of disparate spatial scales associated with the diffusion region and the macroscopic evolution of global system in which the both large-scale magnetic field and bulk plasma dynamics directly influence the reconnection process.…”
supporting
confidence: 77%
“…The present analysis also reveals how some azimuthally narrow dipolarization fronts may be formed. We note that heterogeneity of the magnetotail current sheet might be another way to produce azimuthally narrow dipolarization fronts (e.g., Fujimoto, 2016; Guzdar et al, 2010; Lu et al, 2015). In contrast to the dipolarization fronts released by BICI, such scenarios would need reconnection in the first place.…”
Section: Important Details Of Bici Head Developmentmentioning
confidence: 97%
“…The 3‐D kinetic simulations [ Fujimoto and Sydora , ; Fujimoto , ] have shown that the CSSI has a spatial scale between the ion and electron inertia lengths, i.e., λi1<ky<λe1, where λ s = c / ω p s is the inertia length of species s with ω p s the plasma frequency. The simulation results suggest that both the ion and electron inertias are expected to play a role in the generation of the CSSI.…”
Section: Numerical Analysismentioning
confidence: 99%